OPTIMIZATION OF ENDOSULFAN DEGRADATION BY PSEUDOMONAS AERUGINOSA - VIJAYALAKSHMI P.; USHA M. S. (International Journal of Pharma and Bio Sciences, 2013)
A total of 68 isolates capable of degrading Endosulfan were obtained out of 27 samples collected. Among them 28 isolates showed better efficiencies in degrading Endosulfan as compared to others. Isolate ENS10 which showed 42% degradation of Endosulfan under unoptimized condition was identified as Pseudomonas aeruginosa. After optimization process it was able to show 100% degradation of chlorpyrifos at pH 7, temperature 35°C, pesticide concentration of 2%, 10 ml of inoculum size, shaking speed of 150 rpm and in the presence of 200 mg/l glucose and 300 mg/l peptone.